Simulations of chalcopyrite/c-Si tandem cells using SCAPS-1D. (15th March 2017) - Kim, Kihwan; Gwak, Jihye; Ahn, Seung Kyu; Eo, Young-Joo; Park, Joo Hyung; Cho, Jun-Sik; Kang, Min Gu; Song, Hee-Eun; Yun, Jae Ho
Graphical abstract: We present SCAPS-1D simulations of 2-junction tandem cells with chalcopyrite top subcells with various bandgaps and a c-Si bottom subcell using realistic input parameters. Highlights: Performances of CIGS/c-Si tandem solar cells are simulated by the SCAPS-1D program. The Eg values of the top CIGS cells are set to be from 1.4 to 1.7 eV (ΔEg  = 0.1 eV). The CIGS cell is thinned to yield the same JMPP or JSC to that of the c-Si cell. The 1.6- and 1.7-eV CIGS top cells (t ⩾ 0.2 μm) exhibit current matching conditions. The improvement of top wide-bandgap CIGS cells is a key for further improvement. Abstract: In this work, we present SCAPS-1D simulations of dual-junction tandem cells with chalcopyrite top subcells with various bandgaps (Eg  = 1.4, 1.5, 1.6, and 1.7 eV) and a c-Si bottom subcell. The purpose of these simulations is to assess achievable device performances with a CIGS/c-Si tandem structure when a realistic efficiency of each subcell is applied. The top subcell conditions are simulated based on the state-of-the-art records, and the bottom c-Si cell is designed to have an efficiency of approximately 19%. When the Eg of the top chalcopyrite cell is below 1.5 eV, the current matching condition between the top cell and bottom cell is not obtained until the top cell's thickness is 0.2 μm. However, with Eg values of the top chalcopyrite cells at 1.6 eV and 1.7 eV, the current matching conditions could be found. Nevertheless, because the efficiency from the top chalcopyrite cell is approximately 12%, it is predicted that the tandem structure exhibits a similar device performance to the bottom c-Si cell. This result suggests that improving the efficiency of the wide bandgap cell is essential for the tandem cell to overcome the efficiency form a single-junction solar cell.